DEVELOPMENT OF NATURAL SCIENCES LEARNING VIDEOS BASED ON LOCAL WISDOM OF SASAMBO (SASAK, SAMAWA, MBOJO) FOR ELEMENTARY SCHOOL STUDENTS - Ilham Handika; Asri Fauzi (PROGRES PENDIDIKAN, 2023)
This study aims to develop natural science learning video media based on sasambo local wisdom for elementary school students that is suitable for use in learning based on aspects of validity, practicality, and effectiveness. This research is included in development research (R&D) with the development model used is the 4-D model with 4 stages, namely define, design, development, and disseminate. The instrument used in this study is a validation instrument consisting of media expert validation instruments and material expert validation. Data analysis techniques in this study were analyzed descriptively quantitatively. Data from the validity and practicality questionnaires in the form of numerical scores were converted to qualitative data to be described in five categories. While the aspect of effectiveness is seen based on the results of students' learning tests. The results of this study indicate that the results of the assessment of the media expert validator obtained a score of 44 with very valid criteria, while the material expert validator's assessment obtained a score of 38 with valid criteria. Then the results of the teacher's assessment obtained a score of 78 which was in the range of effective criteria and the learning outcomes of students who fulfilled the KKM were 80% or 13 out of 15 students. Based on these results, it can be concluded that the science learning video media based on local wisdom sasambo is feasible to use.